Pengaruh Content Marketing Tiktok terhadap Minat Beli @Somethincofficial Melalui Brand Awareness - Yunani, Akhmad; Kamilla, Zahra Nadira (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted to determine the effect of TikTok content marketing on buying interest at @somethincofficial through brand awareness. The purpose of doing this research is to find out and analyze how content marketing, buying interest, and brand awareness at @somethincofficial, the magnitude of the influence of brand awareness mediates TikTok content marketing on buying interest at @somethinkofficial. This research was conducted on Somethinc and TikTok users in Indonesia. The population size is not known using a non-probability sampling technique with purposive sampling. The sample of respondents was determined by the Cochran formula and a sample of 385 respondents was obtained. This study used a quantitative method with a descriptive analysis method and causal relationships using a path analysis model with data analysis using IBM SPSS Statistics 23 software. The results of the descriptive analysis in this study on the content marketing variable got a percentage of 83%, the purchase intention variable was 82%, and the brand awareness variable was 85%. The results of this study indicate that TikTok content marketing has a significant effect on purchase intention @somethincofficial, TikTok content marketing has a significant effect on brand awareness @somethincofficial, brand awareness has a significant effect on purchase intention @somethincofficial, brand awareness mediates TikTok content marketing on interested in buying @somethincofficial. Keywords: Content Marketing; Purchase Intention; Brand Awareness.